Editorial - Ratnavadivel, Nagendralingan; Nagappan, Rajendran; Saravanan, Gopinathan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
There is currently a world-wide concern over the quality and relevance of education in schools and they are inevitably at the heart of contemporary debate on public education. The current global trends place emphasis on knowledge as the main capital for the development of the individual and the nation. The development of knowledge depends very much on creative, innovative and enterprising human capital. The role of teachers in developing a knowledge based society is of prime concern to the nation. The ability to think critically and creatively and to reason logically, among other skills, constitute the template for developing a nation that will be able to not just adopt or adapt borrowed knowledge but that which will be able to create and market its own knowledge. It is in this context that it is crucial for teachers to continuously improve the quality of their practice. Inquiry-based teaching grounded on empirical foundations have become a necessity in the ‘new teacher education’.